2016
DOI: 10.2214/ajr.15.15193
|View full text |Cite
|
Sign up to set email alerts
|

Potentially Important Extracolonic Findings at Screening CT Colonography: Incidence and Outcomes Data From a Clinical Screening Program

Abstract: Objective The impact of detection of extracolonic findings at screening CT colonography (CTC) remains controversial. Our objective is to analyze the incidence and outcomes of unsuspected potentially significant (C-RADS extracolonic category E4) findings in a clinical CTC screening population. Methods Over 98 months (April 2004 – June 2012), 7,952 consecutive asymptomatic adults (mean age 56.7 ± 7.3 years, 3,675 men, 4,277 women) underwent first-time screening CTC. Examinations were prospectively interpreted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
15
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 22 publications
(25 reference statements)
7
15
1
1
Order By: Relevance
“…As noted, a separate sub-cohort of this screening population was previously reported on by Pooler, et al (C-RADS category E4 extracolonic findings). [11] Exclusion criteria again included a history of colorectal cancer, known inflammatory bowel disease, known polyposis syndromes, and a history of colorectal surgery. All examinations were prospectively interpreted by a board-certified radiologist practicing within our abdominal imaging section.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted, a separate sub-cohort of this screening population was previously reported on by Pooler, et al (C-RADS category E4 extracolonic findings). [11] Exclusion criteria again included a history of colorectal cancer, known inflammatory bowel disease, known polyposis syndromes, and a history of colorectal surgery. All examinations were prospectively interpreted by a board-certified radiologist practicing within our abdominal imaging section.…”
Section: Methodsmentioning
confidence: 99%
“…[9] Nonetheless, the perceived lack of understanding of the ramifications of these extracolonic findings has been cited as a reason for exclusion of CTC from some U.S. national colorectal cancer screening guidelines. [10] In an effort to address this perceived deficiency in the literature, our research group recently published findings from a large, single-center clinical screening program detailing the incidence and outcomes of concerning or potentially important extracolonic findings,[11] which are classified as C-RADS category E4 according to the definitions established by the Working Group for Virtual Colonoscopy in 2005. [12] We found that C-RADS category E4 extracolonic findings were uncommon at screening CTC (2.5% of patients), but that nearly 70% of these findings represented clinically significant diagnoses, including a large number of frank or potential malignancies, with very few patients undergoing unnecessary further workup.…”
Section: Introductionmentioning
confidence: 99%
“…Current CT technology affords high-resolution images with extremely low X-ray doses, and is therefore considered safe for routine screening and clinical practice (4)(5)(6)(7)(14)(15)(16). Helical scanning, as employed in MDCT, provides data from which detailed 3-D CT images can be reconstructed.…”
Section: Discussionmentioning
confidence: 99%
“…Due to advances in diagnostic imaging equipment, computed tomography (CT) is widely used for diagnosis and screening examinations (4)(5)(6)(7). In particular, multi-detector-row CT (MDCT) can provide three-dimensional (3D) CT images (8) of face and body shape, as well as subcutaneous structures (4,5,9,10).…”
mentioning
confidence: 99%
See 1 more Smart Citation